A new directional relay algorithm for the protection of transmission network systems using discrete wavelet transforms - Ngaopitakkul, A.; Kaitwanidvilai, S. (My University, 2010)
This paper proposes a novel directional relay algorithm to protect transmission network systems with an application of discrete wavelet transform (DWT). The fault signals are simulated using PSCAD/EMTDC. The coefficients of the positive sequence current obtained from each bus are compared in order to identify the direction of fault signals. The coefficient ratio between buses that the fault occurred is calculated so that the proper protective relay sequence can be selected. The result is shown that the algorithm is capable of performing the fault detection as well as arranging the protective relay sequence, with accurate results. ©2010 IEEE.
Keywords: Protective relay sequence; PSCAD/EMTDC; Transmission network systems; Wavelet transform